2004
DOI: 10.2136/vzj2004.0763
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Unsaturated Zone in Artificial Recharge at San Gorgonio Pass, California

Abstract: The hydrogeology of the unsaturated zone plays a critical role in determining the suitability of a site for artificial recharge. Optimally, a suitable site has highly permeable soils, a capacity for horizontal flow at the aquifer boundary, a lack of impeding layers, and a thick unsaturated zone. The suitability of a site is often determined by field and laboratory measurements of soil properties, field experiments, and numerical modeling. An artificial recharge site in the San Gorgonio Pass area in southern Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 7 publications
(9 reference statements)
1
29
0
Order By: Relevance
“…Most recent perched-water zone studies have been conducted in the context of contaminant transport; however, the effects of perching phenomena are also of interest in artificial recharge efforts (Flint et al 2004(Flint et al , 2012 and for lateral flow on hillslopes (Uchida et al 2004) and reclaimed soils (Kellin et al 2004). Generally, artificial recharge projects apply water in surface and near-surface spreading locations, using the vadose zone to transport and store water.…”
Section: Overview Of Perched Water Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Most recent perched-water zone studies have been conducted in the context of contaminant transport; however, the effects of perching phenomena are also of interest in artificial recharge efforts (Flint et al 2004(Flint et al , 2012 and for lateral flow on hillslopes (Uchida et al 2004) and reclaimed soils (Kellin et al 2004). Generally, artificial recharge projects apply water in surface and near-surface spreading locations, using the vadose zone to transport and store water.…”
Section: Overview Of Perched Water Literaturementioning
confidence: 99%
“…Generally, artificial recharge projects apply water in surface and near-surface spreading locations, using the vadose zone to transport and store water. Flint et al (2004) used a numerical analysis to demonstrate that recharge of the regional aquifer at San Gorgonio Pass, California, could be ineffective because most of the injected water would remain above a large perching zone, considerably delaying and limiting recharge to occur in relatively small areas. A follow-up study (Flint et al 2012) showed that, after actual infiltration of almost 4 million m 3 of water, vertical aquifer recharge was considerably larger than predicted.…”
Section: Overview Of Perched Water Literaturementioning
confidence: 99%
“…With such approaches use is made of some measured vadose zone property which is modelled using a transport model in which the travel time is considered, directly or indirectly, as the fitting model parameter. With the inverse approach, measured moisture content or resident tracer profiles have been used as fitting data by Wang et al [49], McElroy and Hubbell [32], Hubbell et al [17], Flint and Ellett [13] and Wu et al [50]. Robinson et al [39] combines measurements of moisture content with the analysis of a tracer experiment.…”
Section: Introductionmentioning
confidence: 99%
“…Water infiltrated from ponds in areas underlain by thick unsaturated zones having less permeable deposits than those found along major streams and rivers may be a feasible method of recharging underlying alluvial aquifers. Some of the difficulties inherent with this approach and the role of thick unsaturated zones in artificial recharge were studied numerically by Flint and Ellett (2004). However, few field‐scale experiments are reported in the literature describing the movement, and associated changes in quality, of water infiltrated from ponds through thick, heterogeneous unsaturated zones.…”
Section: Introductionmentioning
confidence: 99%